The Protective Role of Salmonella Typhimurium-Whole Sonicated Killed Antigen and Syzygium aromaticum Extract on the Histopathological Changes Against Its Infection in Rabbits - Al-Juburi, Linah I; AL-Sammarraae, Ikram A (The Iraqi Journal of Veterinary Medicine, 2022)
This research aimed to evaluate the protective ability of Syzygium aromaticum methanolic extract against Salmonella Typhimurium infection in rabbits. Three groups of eight rabbits were given the following: The first group was subcutaneously given SalmonellaTyphimurium-whole sonicated killed antigen (ST-WSKAg); the second group was orally given S. aromaticum extract as well as KWCSAg-ST subcutaneously; the third group was left as positive control group. The rabbit groups were orally challenged by 9×108 CFU/mL Salmonella Typhimurium then the animals were sacrificed 10 days postchallenge for histopathological study. Intestine, liver, kidney, and spleen were studied for pathological changes. The results showed that the second group had the least histopathological changes with mild inflammation and cellular infiltration of inflammatory cells, as well as low amount of vacuolation. The ST-WSKAg group showed multifocal aggregation of inflammatory cells and inflammation of all organs studied, as well as slight interstitial edema with few cellular infiltration and cystic tubular dilation of neighboring tubules in kidney. The positive control group showed the most extensive signs of destruction, severe inflammatory cells infiltration, as well as existence of live bacterium in tissue. In conclusion, Syzygium aromaticum extract showed to give a suitable protective ability against inflammation and destruction of virulent Salmonella Typhimurium infection in comparison to both of ST-WSKAg and positive control groups